The Impact of Behavioral Biases on Investment Performance: Does Financial Literacy Matter? - Lebdaoui, Hind; Chetioui, Youssef; Guechi, Elias (International Journal of Economics and Financial Issues, 2021)
This paper aims to investigate the impact of behavioral biases and financial literacy on investment performance in an emerging stock market context. Based on data collected from a sample of 196 Moroccan investors operating in Casablanca stock exchange, we test the research hypotheses using structural equation modeling. Out of the four heuristics examined in our proposed conceptual framework (i.e. overconfidence, representativeness, anchoring and herding), only overconfidence and representativeness had a significant positive impact on financial performance. Our results also suggest a significant positive impact of financial literacy on representativeness, while it was found negatively associated with overconfidence. This research paper is the first of its kind to investigate the existence of heuristics in an African, Arab and emerging market. As well, the current study is among the earliest attempts to examine how behavioral biases relate to investors performance. Keywords: Heuristics; financial literacy; investment performance; stock market; SEM. JEL Classification: G02. DOI: https://doi.org/10.32479/ijefi.11318